French Translation and Validation of the Synkinesis Assessment Questionnaire. (22nd May 2021) - Martineau, Sarah; Gascon, Laurence; Saltychev, Mikhail; Rahal, Akram; Marcotte, Karine; Moubayed, Sami P.
ABSTRACT: Synkinesis is a distressing sequela of peripheral facial palsy (PFP). This study aimed to translate and validate the Synkinesis Assessment Questionnaire (SAQ), a reliable patient-reported outcome evaluation tool for synkinesis, in French. The SAQ was translated following a standard forward–backward translation procedure. After a cognitive debriefing with 10 PFP patients, the SAQ-F was assessed amongst 50 patients for internal consistency, known-group validity, construct validity, criterion validity, and test–retest reliability. Results demonstrated that the SAQ-F was valid, reliable, and had a unidimensional structure. The SAQ-F should be accompanied by clinician-based scales, to provide valuable additional information on the severity of synkinesis.